Law Enforcement Against Children as Perpetrators of Murder In Medan City - Sinaga, Mhd. Sanip Heri; Firman Halawa; Yasmirah Mandasari Saragih (International Journal of Contemporary Sciences (IJCS), 2024)
Criminal acts committed by children have laws and regulations that contain rules regarding the provision of sanctions against the perpetrators as stipulated in Law Number 23 of 2002 concerning child protection jo. Law Number 35 of 2014 concerning amendments to Law Number 23 of 2002 concerning Child Protection, with the juvenile justice system as stipulated in Law Number 11 of 2012 concerning the Criminal Justice System. This research uses empirical juridical methods. The results showed that the criminal act of murder committed by children is very concerning and the application of laws and regulations to children as perpetrators of criminal acts is still ineffective, does not cause a deterrent effect or fear effect on other children, so that there is still an incidence of criminal acts of murder committed by children every year. Therefore, it is necessary to conduct coaching and direction for children so that they do not choose the wrong association and are not wrong in taking actions so that later they can become good successors of the nation for the progress of the country as expected